2004
DOI: 10.1021/bi049485k
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Specific Escherichia coli SecY−Signal Peptide Interaction

Abstract: Protein translocation in Escherichia coli is initiated by the interaction of a preprotein with the membrane translocase composed of a motor protein, SecA ATPase, and a membrane-embedded channel, the SecYEG complex. The extent to which the signal peptide region of the preprotein plays a role in SecYEG interactions is unclear, in part because studies in this area typically employ the entire preprotein. Using a synthetic signal peptide harboring a photoaffinity label in its hydrophobic core, we examined this inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…In addition, the presence of nucleotide reduces further the affinity of lipid-bound SecA for the signal peptide, consistent with ADP binding inhibiting the endothermic conformational transition of SecA (30). In the context of translocation, this may help to ensure that one consequence of SecA-signal peptide membrane insertion is release of the signal peptide for interaction with SecY (13).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, the presence of nucleotide reduces further the affinity of lipid-bound SecA for the signal peptide, consistent with ADP binding inhibiting the endothermic conformational transition of SecA (30). In the context of translocation, this may help to ensure that one consequence of SecA-signal peptide membrane insertion is release of the signal peptide for interaction with SecY (13).…”
Section: Discussionmentioning
confidence: 76%
“…microscopy, that oligomers of SecYEG form protein-conducting channels in lipid bilayers that are sufficiently wide to accommodate part of SecA with the preprotein, yet the recent Xray structure of SecYEG (12) revealed that the channel is too small to allow insertion of SecA; rather, the SecYEG pore is large enough only for preprotein incorporation, consistent with signal peptide recognition by SecYEG (13).…”
mentioning
confidence: 99%
“…7,20 The photoactive analogue of this peptide, in which phenylalanine was substituted by ρ-benzoylphenylalanine (Bpa), MKQSTIALALLPLL(Bpa) TPVTKAC-NH 2 , was chemically synthesized and biotinylated by thiol linkage with cysteine as described by Wang et al 19 The activity of the peptide was confirmed by measuring the extent of stimulation of SecA-lipid ATPase activity as described previously. 5,7…”
Section: Signal Peptidesmentioning
confidence: 99%
“…The associated cholesterol is then esterified by lecithin cholesterol acyl transferase and the HDL particles undergo a structural change, going from discoidal to spherical in shape. 19 Nanodiscs are protein-lipid particles which are engineered to mimic nascent discoidal HDL particles. They are produced in order to create a platform in which to embed and solubilize membrane proteins in a native lipid environment.…”
Section: Introductionmentioning
confidence: 99%